Photocaged Carbohydrates: Versatile Tools for Controlling Gene Expression by Light - Bier, Claus; Binder, Dennis; Drobietz, Dagmar; Loeschcke, Anita; Drepper, Thomas; Jaeger, Karl-Erich; Pietruszka, Jörg (Synthesis, 2017)
The control of biological processes plays a central role in life science, especially the tight regulation of gene expression for biotechnological systems. In this context, optogenetic tools have emerged as an important instrument for controlling gene expression by light with high spatiotemporal resolution in a non-invasive way. Here, we present the syntheses and characterization of biofunctional photocaged carbohydrates, on the basis of the biologically most relevant carbohydrates glucose, galactose, rhamnose, and lactose. The single-step cleavage of these compounds allows both, to rapidly activate and temporary or permanently repress the transcription in E. coli after short UV-A light exposure. This study thus presents a versatile toolbox of photocaged carbohydrates for the light-triggered regulation and control of cellular processes useful for synthetic bio(techno)logy applications.
Keywords: caged compounds; carbohydrates; optogenetics; bacterial gene expression; photo-removable protection group; biotechnology